The Development Of "Remine Me" Vibrating Watch Media For Optimization Of Interaction And Communication In Deaf Students - Novtasari, Rianti; Utami, Ratna Tri; Musiman, Musiman; Yansyah, Medi (JPK (Jurnal Pendidikan Khusus), 2023)
This research was motivated by communication problems between lecturers and the subjects' peers who had difficulty calling and talking when studying offline. This happens because when you want to start communicating or simply call a subject, because the subject cannot hear you need to be approached first and "patted" so that the subject is sensitive and focused that someone wants to communicate with him. This research aims to produce a tool that can bridge communication between deaf students and stakeholders during learning. Therefore, the vibrating watch was designed to increase sensitivity in deaf students, this watch was named "Remine Me". This "Remine Me" vibrating watch works by capturing sensors with the help of a remote control, then the sensors will transmit stimulation in the form of vibrations to the hands of deaf students, so that if they want to communicate with the subject while they are still at a certain distance, this will make it easier for deaf students and lecturers. even with peers to be able to start communication without having to be "patted" first. The development in this research uses the R&D research method with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) design. The research subject was a 3rd semester deaf student. The result of this development was a vibrating watch with remote control. The results of the development of "Remine Me" could be an alternative tool that can be used by every lecturer to make it easier to call deaf students in their class.